Digitally melting cities under climate stress - Ünsal Özdilek (Discover Cities, 2025)
Abstract Urban land-use planning has traditionally assumed that core functions—industry, housing, office, and retail—require expansive, permanent physical footprints. This physicality paradigm, inherited from the beginning of organized urbanism, is now challenged by rapid digitization and intensifying environmental and climate pressures. Increasingly, tasks once anchored to factories, offices, and storefronts migrate to automated, remote, or virtual platforms, undermining the notion that physical expansion must track economic or social progress. Confronted with global urbanization and looming climate emergencies, digitization compels a reevaluation of how cities allocate land, consume resources, and protect vulnerable communities. This paper introduces a dynamic “meltdown” framework for understanding how digitization systematically erodes structural reliance, thereby freeing or repurposing land for adaptive reuse. Drawing on spatio‐temporal big data from sensor networks, remote sensing, geographic information systems, and occupant analytics, we examine how key urban tasks—production, commerce, administration, and residency—can be quantified for “meltability” based on physical anchorage, digital capacity, and environmental constraints. Our model demonstrates that meltdown not only diminishes structural demand but also opens opportunities for greener infrastructure, such as flood buffers or urban forests, thus enhancing climate resilience. By integrating real‐time data and occupant‐centered metrics, planners and policymakers can anticipate where and when digital alternatives render conventional land uses obsolete, proactively converting those areas to more sustainable or socially beneficial functions. In doing so, this research transcends conventional “smart city” optimization, revealing how occupant activities disrupt once‐immutable footprints and forging a data‐driven path to reduce carbon emissions, strengthen ecosystem services, and help equitable, knowledge‐driven urban development under mounting climate challenges.